2016
DOI: 10.17549/gbfr.2016.21.1.56
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships among Strategic Performance Measurement Systems, IS Strategic Alignment, and IT Infrastructure for Knowledge Management

Abstract: A B S T R A C TInvestigating how to develop information technology (IT) infrastructure that can effectively facilitate knowledge management (KM) activities has been an important research area. To contribute to the theoretical and practical developments in this research area, this study empirically examined the causal relationships among the use of strategic performance measurement systems (SPMS), organizational learning, information systems (IS) strategic alignment, IT infrastructure for KM, competitive applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The results imply that the impact of strategy on firm performance is indirect and path-dependent, and strongly relates to an effective interaction between the intended outcomes and how strategies are implemented. Notwithstanding the arguably key role of corporate, operational, or IS strategies in determining firm performance (Balau, 2015;Choe, 2016), our research suggests that any strategy per se is not enough, but it is rather an intentionally strategic alignment which will significantly impact performance. Moreover, although the strategic triad proposed by Pearlson, Saunders, & Galletta (2019) is indeed an important determinant of a firm's performance and competitiveness, it seems that it is the alignment of corporate and IS strategies which more clearly Our study has limitations.…”
Section: Discussionmentioning
confidence: 82%
“…The results imply that the impact of strategy on firm performance is indirect and path-dependent, and strongly relates to an effective interaction between the intended outcomes and how strategies are implemented. Notwithstanding the arguably key role of corporate, operational, or IS strategies in determining firm performance (Balau, 2015;Choe, 2016), our research suggests that any strategy per se is not enough, but it is rather an intentionally strategic alignment which will significantly impact performance. Moreover, although the strategic triad proposed by Pearlson, Saunders, & Galletta (2019) is indeed an important determinant of a firm's performance and competitiveness, it seems that it is the alignment of corporate and IS strategies which more clearly Our study has limitations.…”
Section: Discussionmentioning
confidence: 82%
“…12 However, information systems strategies need to be aligned with other business strategies, so that the development of IT-infrastructures is clear for everyone in the organization. 13 Leadership support is required to promote positive policies and a sense of readiness, as opposed to being resistant to change. 14 Learning is necessary for organisations, 15 and note an increase in the use of mobile technologies in the education sector have increased.…”
Section: Organizational Learningmentioning
confidence: 99%
“…Romjin & Albaladejo (2002) emphasized the importance of corporate owned R&D as an important source of innovation and Yam et al (2004) divided the learning capacity, R&D capacity, resource allocation capacity, manufacturing capacity, marketing capacity, organizational capacity, and strategic planning capacity into the factors of technological innovation ability. Choe (2016) observed that the competitive usage of knowledge asset had a positive impact on the performance of an organization. Moon (2017) confirmed in his study that a CEO's technically oriented functional background affected the firm's technological innovation performance.…”
Section: A Literature Reviewsmentioning
confidence: 99%